Strongyloides stercoralis HYPERINFECTION IN A RENAL TRANSPLANT RECIPIENT - Venturi, Jakelline; do Livramento, Andréa; Souza Nunes, Zeliana; Karini Rensi Botelho, Tatiani (Revista de Patologia Tropical / Journal of Tropical Pathology, 2019)
Strongyloidiasis is a worldwide intestinal infection produced by the nematode Strongyloides stercoralis. In this study, we report the case of a 47-year-old female patient who was submitted to renal transplant and an immunosuppression regimen. She was admitted to the emergency service with intense abdominal pain, evolving to an acute respiratory insufficiency, gramnegative bacteremia, refractory shock and death. S. stercoralis larvae were identified in the parasitological exam and bronchoalveolar lavage. This provides evidence for the importance of the early diagnosis of this neglected helminthiasis in transplanted patients undergoing immunosuppresive therapy.